ANALISIS LIFE CYCLE ASSESSMENT (LCA) PROSES PRODUKSI SEMEN PADA PERUSAHAAN SEMEN (GATE TO GATE) - Aulia Ulfah Farahdiba; Nonna Shifa Cahaya Delima Handricahyono (EnviroUS, 2022)
Tuban Cement Plant could be a cement plant found in Tuban, East Java. This Cement Manufacturing plant produces cement made from Limestone, Clay, Press Sand, Silica Sand. The coming about item is around 2 million tons of cement. The cement generation forms analyzed incorporate the raw mill, clinkerzation and wrap up process forms. Within the handle of making the item, it does not as it were create the anticipated item but too makes by-products. Hence it is vital to do elective methodologies to diminish the burden of emanations coming about from the generation handle. Natural affect examination caused by the generation handle can utilize the Life Cycle Appraisal (LCA) strategy. In this examination employing a entryway to door approach with SimaPro 9.2.0.1. The affect examination strategy chosen is the Impact 2002+ this strategy may be a strategy that can get comes about that are in agreement with the goals and are close to the conditions that happen within the Tuban Cement Plant environment. The information analyzed in this consider employments generation information for each 1 ton of cement item.